FAKTOR EMERGENCY CASE HIV AIDS DI BOJONEGORO - Susanti, Dwi Agung; Maftukhin, Ahmad; Afandi, Agus Ari (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2019)
ABSTRACT                    AIDS is a group of symptoms characterized by decreased immune system so that all infectious diseases are easy to attack, the cause is the Human Immunology Virus. Patients infected with HIV are considered to get a curse from God, so it is very disturbing psychological sufferers. Some are even ostracized, despised and ridiculed physically and mentally. From year to year HIV cases in Bojonegoro show an increase, HIV AIDS in Bojonegoro such as the "iceberg phenomenon" of HIV / AIDS because the number of HIV AIDS is recorded after patients suffering from opportunistic infections who seek treatment at the hospital, while how many other people have been infected with HIV but it hasn't been detected yet because it doesn't understand the importance of early check. The discovery of new cases is impossible to do easily, because it will increase the high incidence of HIV AIDS in Bojonegoro. Several attempts have been made to control its spread, but the incidence of this disease in Bojonegoro from year to year has increased until 2016, accumulating 884 cases. This study aims to analyze the factors of HIV AIDS emergency case in Bojonegoro.                    This study uses analytic design with Cross Sectional design is a study to study the dynamics of the correlation between risk factors and effect factors, by way of approach, observation. The population of this study were all PLWHA who were examined at the Sehati Polyclinic of RSUD dr. R. Sosodoro Djatikoesoemo Bojonegoro as many as 884. The sample in this study was the majority of PWHA in the same clinic at Bojonegoro Regional Hospital using systematic random sampling technique. The independent variables in this study are: Stigma and discrimination, Distance between the service polyclinic and PWHA. Community support (PWHA reference group (fellow PWHA); community leaders), Family support. The dependent variable that is suspected to be the cause of an emergency case for the high transmission of HIV AIDS is the risk behavior for HIV AIDS transmission                    The results showed no significance where ? was greater than 0.05, so there was no relationship between the factors of stigma and discrimination, distance between the house and the clinic, community support and family support for HIV AIDS transmission risk behavior in Bojonegoro and there were no dominant factors in risk behavior for HIV AIDS transmission in Bojonegoro.The active role of health workers and related institutions is very important in preventing the risk of HIV AIDS transmission in Bojonegoro. Government programs on preventing HIV AIDS transmission must be increased to reduce cases of HIV AIDS. Keywords: emergency case, community stigma, risk behavior, logistic regression